(untitled) (Journal of Partial Differential Equations, 1996)
We will investigate the point spectrum on the imaginary axis of the linearized Boltzmann operator with an external-force potential in a bounded domain whose boundary is sufficiently smooth. The boundary condition considered is the perfectly reflective boundary condition. The point spectrum on the imaginary axis is only equal to 0. However, the null space varies with the common axes of symmetry of the domain and the external-force potential.